Media Pembelajaran Interaktif “SIBUDAYA” (Keragaman Budaya) Berbasis Self Instructional pada Muatan IPAS Kelas IV Sekolah Dasar - Aprilia, Ni Wayan Yeni; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Jurnal Media dan Teknologi Pendidikan, 2025)
This research is motivated by the issue that the topic of cultural diversity in the IPAS subject at the elementary school level has a broad and complex scope, making it difficult for students to understand. This study aims to develop and test the effectiveness of an interactive learning media based on Self-Instructional principles. The development model used in this research is the ADDIE model, which consists of five stages. The research trial subjects comprised 32 fourth-grade elementary school students. The data analysis methods used include qualitative analysis, quantitative analysis, and inferential statistics to measure the effectiveness of the product. The feasibility test results of the interactive media "SIBUDAYA" received an excellent rating, with a feasibility percentage of 93.75% from material experts, 91.66% from design experts, and 97.22% from practitioners. The individual trial among students obtained a score of 88.13%, while the small group trial reached 87.03%, indicating that this media is highly suitable for use in learning. The effectiveness of this interactive media was tested through a post-test, where the t-test calculation results showed that the tvalue = -149.59 was significantly greater than the ttable value = 2.04. Therefore, it can be concluded that this learning media is effective in helping students understand the topic of cultural diversity in IPAS and improving their learning outcomes.